Framing Malaysia heritage through the lens of online media - Abdullah, Karmilah; Tan, Poh Ling (Human Resource Management Academic Research Society, 2023)
The heritage of a country provides clues to its past and how its society has evolved over time. Heritage includes both tangible and intangible aspects of the country. Existing research on heritage by the mass media has primarily focused on tourism, historical conservation, or landscape value in particular. Thus, there is a lack of studies looking at other valuable heritage issues in the country. This study adopts framing analysis to determine the representational dynamics employed in online news articles on heritage issues in Malaysia. Data were collected during the study timeframe from online newspapers in Malaysia between January and July 2022, and it was found that 176 articles covered Malaysia’s heritage. The findings show that English language news portals published the highest rate of heritage news. Heritage news was mostly published as straight news type of news and used authority as the main source of information. This study identifies two frames, which are tangible and intangible heritage. The findings of the study are essential for creating awareness among the public about the different types of cultural heritage available in the country.